Board structure and extent of corporate governance statement. (4th October 2010) - Amran, Azlan; Ishak, Mohd Syarizal; Zulkafli, Abdul Hadi; Nejati, Mehran
The board of directors is an important entity in a company, creating a link between shareholders and managers and therefore playing an important role in the governance of a firm. This study focuses on board structure and the extent of the corporate governance statement disclosure. This study found that the size of the corporate board does have some influence on the extent of the corporate governance statement disclosure. It is quite surprising to find that the rest of the variables involving the board structure do not have any association with the extent of corporate governance statement.